2006
DOI: 10.5194/nhess-6-519-2006
|View full text |Cite
|
Sign up to set email alerts
|

Influence of rheology on debris-flow simulation

Abstract: Abstract. Systems of partial differential equations that include the momentum and the mass conservation equations are commonly used for the simulation of debris flow initiation, propagation and deposition both in field and in laboratory research. The numerical solution of the partial differential equations can be very complicated and consequently many approximations that neglect some of their terms have been proposed in literature. Many numerical methods have been also developed to solve the equations. However… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(23 citation statements)
references
References 16 publications
2
21
0
Order By: Relevance
“…It was found that the yield stress, roughness coefficient n and volumetric sediment concentration have a relatively large influence on the simulated results as compared with other testing parameters. The result is identical to that of other researches (Lin et al, 2005;Arattano et al, 2006;Sosio et al, 2007).…”
Section: Sensitivity Analysissupporting
confidence: 90%
“…It was found that the yield stress, roughness coefficient n and volumetric sediment concentration have a relatively large influence on the simulated results as compared with other testing parameters. The result is identical to that of other researches (Lin et al, 2005;Arattano et al, 2006;Sosio et al, 2007).…”
Section: Sensitivity Analysissupporting
confidence: 90%
“…Their flow characteristics depend on the water content, sediment size and/or sorting, and on the dynamic interaction between the solid and fluid phases (Pirulli et al, 2008). In particular, the rheological properties naturally change, even during a single debris-flow event (Remaitre et al, 2005) or still for debris flows taking place in the same torrent (Arattano et al, 2006). Even if there are so many variabilities and uncertainties in the choice of the rheological parameters, they are generally required by numerical models to replicate debris-flow events, and the models outcome are very sensitive to the wide variability of them (Arattano et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…In particular, the rheological properties naturally change, even during a single debris-flow event (Remaitre et al, 2005) or still for debris flows taking place in the same torrent (Arattano et al, 2006). Even if there are so many variabilities and uncertainties in the choice of the rheological parameters, they are generally required by numerical models to replicate debris-flow events, and the models outcome are very sensitive to the wide variability of them (Arattano et al, 2006). This implies that, for purposes of hazard prediction and assessment on a debris fan, different simulations have to be performed assuming different rheological behaviours and exploring the related consequences (Arattano et al, 2006).…”
Section: Resultsmentioning
confidence: 99%
“…It is based on the solution of the conservation of mass and momentum equations and uses a quadratic rheological model defining the flow pattern of the mixture both for a viscous fluid and for a turbulent/dispersive fluid. The resistant term of the Saint Venánt equations has a higher influence on reproducing debris-flows than the other terms (Arattano et al [20]), so it should be adequately estimated. The rheological behavior of a debris-flow containing coarse particles cannot be assessed considering exclusively the contribution of the finer matrix (silt and clay) and thus neglecting the effects of direct grain contacts (Sosio et al [21]).…”
Section: Debris-flow Modelingmentioning
confidence: 99%